PREVALENCE OF SMALL DENSE LDL IN TYPE 2 DIABETES MELLITUS AND ITS CORRELATION WITH INFLAMMATORY MARKERS: A COMPREHENSIVE STUDY - ANUSH N; SUKHDEEP KUMAR; RIJU MATHEW; PRANAV KUMAR PRABHAKAR (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This research pursues to determine the incidence of elevated levels of sdLDL in T2DM patients and study its association with inflammatory biomarkers, including high-sensitivity C-reactive protein (hsCRP), lipoprotein-associated phospholipase A2 (Lp-PLA2), and red cell distribution width (RDW). Methods: The study involved 158 participants, comprising both diabetic and non-diabetic individuals, recruited from a tertiary care facility. Blood samples underwent analysis for sdLDL levels using a two-step enzymatic technique. Inflammatory markers were estimated using nephelometry and chemiluminescent immunoassays. SPSS was employed for statistical analysis to establish relationships and significance levels. Results: Diabetic subjects demonstrated particularly higher sdLDL levels than non-diabetic controls (p < 0.001). A robust positive correlation was identified between sdLDL and hsCRP, Lp-PLA2, and RDW, suggesting a connection between sdLDL and systemic inflammation. Regression analysis further substantiated that elevated inflammatory marker levels were linked to increased sdLDL concentrations. Conclusion: The outcomes underline the crucial role of sdLDL in diabetic dyslipidemia and its strong relationship to inflammation. Estimation of sdLDL levels along with inflammatory biomarkers may improve cardiovascular risk assessment in diabetic patients. Therapeutic interventions, including lipid-lowering and anti-inflammatory approaches, could possibly reduce sdLDL-induced atherosclerosis.